Restrições entrópicas em cosmologias quase-topológicas - Lima, Andre Luiz Alves (2013)
We present a teaching sequence developed with STSE approach that aimed to develop important aspects of scientific literacy in high school students, which was developed during the first half of 2015, in a class of 40 students the first year of education East, the morning shift, the State School Aristobulo Barbosa Leão, located in Serra / ES. The STSE approach, and boost critical and reflective questions, has a functional structure that facilitated the organization of 19 classes that make up the instructional sequence, entitled "energy sources and their environmental and social impacts: evaluating costs and benefits." We chose to open questions, collective reading texts, videos consideration and discussion of issues related to them in the search for more interactive and dialogical classes. The qualitative study aimed to investigate the potential of educational intervention in the context of physical education, from the pursuit of scientific literacy of evidence in the arguments produced by the students, analyzing the quality of these arguments and epistemological present operations on them. The data were collected from the following sources: teacher logbook classes in video recordings, audio recordings of conversations, copy the written activities and interview recorded audio. The choice of a social-controversial issue as the issue of intervention and starting point of the STSE approach contributed to the success of educational intervention, since data analysis allowed us to conclude that the teaching sequence was able to contribute to scientific literacy process students and provided development of their argumentative skills. In addition to the dissertation research provided the preparation of a final product, which is developed instructional sequence and has reports of very rich experiences that occurred in me for your application